Porous microstructures induced by picosecond laser scanning irradiation on stainless steel surface. (March 2016) - Liu, Bin; Jiang, Gedong; Wang, Wenjun; Mei, Xuesong; Wang, Kedian; Cui, Jianlei; Wang, Jiuhong
Abstract: A study of porous surfaces having micropores significantly smaller than laser spot on the stainless steel 304L sample surface induced by a picosecond regenerative amplified laser, operating at 1064 nm, is presented. Variations in the interaction regime of picosecond laser pulses with stainless steel surfaces at peak irradiation fluences( F pk =0.378–4.496 J/cm 2 ) with scanning speeds( v =125–1000 μm/s) and scan line spacings( s =0–50 μm) have been observed and thoroughly investigated. It is observed that interactions within these parameters allows for the generation of well-defined structured surfaces. To investigate the formation mechanism of sub-focus micropores, the influence of key processing parameters has been analyzed using a pre-designed laser pulse scanning layout. Appearances of sub-focus ripples and micropores with the variation of laser peak fluence, scanning speed and scan line spacing have been observed. The dependencies of surface structures on these interaction parameters have been preliminarily verified. With the help of the experimental results obtained, interaction parameters for fabrication of large area homogeneous porous structures with the feature sizes in the range of 3–15 μm are determined. Highlights: We present the generation of surface structures on 304L by picosecond laser pulses. Different surface structures are observed using a pre-designed scanning path. Physical mechanisms for nanoripples and micropores are discussed. Controlling peak fluecne is the most effective and directive way for micropores. The surfaces of desired micropores are presented by optimizing laser parameters.